2015
DOI: 10.1186/1475-925x-14-s1-s11
|View full text |Cite
|
Sign up to set email alerts
|

A 3D numerical study of the collateral capacity of the circle of Willis with anatomical variation in the posterior circulation

Abstract: Background: The Circle of Willis (CoW) is the most important collateral pathway of the cerebral artery. The present study aims to investigate the collateral capacity of CoW with anatomical variation when unilateral internalcarotid artery (ICA) is occluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…Increasing intramural pressure on the connective parts of the ACoA complex can initiate the process of remodeling the blood vessel resulting in the formation of an aneurysmal sac and then to its rupture [17]. In an experimental study with rabbits Ersin et al demonstrated the hemodynamic effect of increased perfusion requirements in the formation of aneurysms [24], and Guangyu Zhu and al.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing intramural pressure on the connective parts of the ACoA complex can initiate the process of remodeling the blood vessel resulting in the formation of an aneurysmal sac and then to its rupture [17]. In an experimental study with rabbits Ersin et al demonstrated the hemodynamic effect of increased perfusion requirements in the formation of aneurysms [24], and Guangyu Zhu and al.…”
Section: Discussionmentioning
confidence: 99%
“…An idealized model could be a simple one based on limited geometric parameters [47], a local 3D geometry coupled with 0D artery tree at inlet and outlets [48], or a structure rebuilt from the in-vitro model [49,50]. More patient-specifically, some idealized models were reconstructed from the central lines extracted from the clinical imaging of intracranial arteries [51][52][53] or an intact arterial structure starting from the aorta [5], or derived from changing the topology of CoW reconstructed from patientspecific CT images [54]. In-vivo geometric models were reconstructed exactly from the patient-specific imaging data.…”
Section: ) Methods To Improve Accuracymentioning
confidence: 99%
“…Another physiological variable that is critical to determining outcome is the degree of collateral circulation possessed by stroke victims. [ 17 ] The more perfusion pathways possessed by a given area of the brain, the greater the degree and duration of ischemia necessary to produce damage.…”
Section: Ischemic Stroke and Transient Ischemic Attackmentioning
confidence: 99%